Farmers’ perceptions towards agroforestry systems in Babanosa Area, West Kordofan State - Fadl, Kamal Eldin Mohammed; Ahmed, Ali Elamin Abdallah (International Journal of Environment, 2015)
This study was conducted in Eltemada, Boli and Umghoghai villages at Babanosa area in El-salam locality, South Kordofan State during 2012 and 2013. The objectives were to (1) identify and assess the most important agroforestry systems, (2) to investigate the main factors that affecting the sustainability of the systems, (3) to determine the important field crops that cultivated with trees and (4) to evaluate the effect of the agroforestry systems on the yield of the traditional field crops. For accomplishment of these study 80 questioners was designed and distributed in the selected villages. After the data collection data was analyzed by using descriptive statistic. The results showed that the most important agroforestry systems in the study area are parkland cropping system (58%), boundary planting (26%), wind-breaks (13%) and alley cropping (3%).The most important forest trees in the study area are Acacia senegal (32%), Ziziphus spina- christia (28%), Balanites aegeyptiaca (26%), Sclerocary birrea and Guera senegalensis (3%). The main field crops in the study area are groundnut (44%), sorghum (35%) and roselle (21%). The results showed that yield of groundnut and sorghum is higher under agroforestry systems compared with the mono-cropping system. The results showed that the majority of respondents (70%) prefer to cultivate field crops in agroforestry system, while (30%) prefer to cultivate the field crops in a mono-cropping system. The cultivation methods used in the study area include shifting cultivation (52%), mono-cropping (36%) and intercropping (12%).The majority of respondents (94%) showed that trees improve soil fertility in their farm land. The benefits from trees in farm land include improvement of soil properties (36%), protecting the farm land from wind erosion (28%), improvement of micro-climate (24%) and source of income which was indicated by (12%) of the respondents. The study recommended that modern agroforestry system such as improved fallow system and alley cropping should be introduced in the study area and multi-purpose trees such as Acacia senegal, Fedherbia albida and Sclerocarya birrea that improve soil fertility and diversify farmers income should be maintained. DOI: http://dx.doi.org/10.3126/ije.v4i2.12633 International Journal of Environment Vol.4(2) 2015: 136-146